Road-design and Road-Safety in Surface Mining - Thompson, Roger (Wide Publishing, 2014)
This Chapter identifies and examines the challenges in the mobile equipment and haulage-related activities of the surface mining process, specifically those associated with the design and operation of safe heavy vehicle (haul truck) mining roads. The role of mobile equipment causation in incidents is evaluated in the light of international studies into mine road-safety and –design. The Chapter then continues to outline how the combination of mine haul truck haul road design and established safety audit techniques within the safe-systems approach can be used to reduce accidents in this key component of the mining process.